Gynocriticism As Bolstered On Margaret Atwood's Giving Birth - Galuh Fadhelah Aulia Hamidah; Dewi Ayu Rengganis; Suhartawan Budianto; Rommel Utungga Pasopati (Universitas Dehasen Bengkulu, 2023)
Margaret Atwood is a female author who is known from her works that discuss intertwinement of women's relationships with the world. Giving Birth is one of her short stories published in 1977 that focused on an unnamed female narrator’s story that tells Jeanie’s experience who are preparing and finally undergoing the process of giving birth. Through this short story, the researchers indicated matter of gynocriticism by Elaine Showalter that describes women as writers. It also included matter of soul and psychoanalytic approach. Through qualitative method, this research underlines how giving birth is specific experience felt only by women from the existence of the womb. Pregnancy is the best experience of woman that could define herself as the main author of the future adventure of her baby. In conclusion, underlining gynocriticism in Giving Birth indicated true matters of identity of women beings. Then, the criticism also shows how those shape differences between male and female kind of literature.